PENGGUNAAN Hydrilla verticillata SEBAGAI FITOREMEDIATOR DALAM PEMELIHARAAN IKAN PATIN (Pangasius sp.) - Annisa Siregar; Dade Jubaedah; Marini Wijayanti (Jurnal Akuakultur Rawa Indonesia, 2017)
ABSTRACT Fitoremediation is one of water quality management system by using water plant such as Hydrilla verticillata that is purposed to decrease organic materials. This research was conducted at Laboratorium Dasar Perikanan, Aquaculture Study Program, Faculty of Agriculture, Sriwijaya University,Indralaya on May – July 2016. The research based on a Completely Randomized Design with four treatments and three replications. The treatments were media without H. verticillata (P0), addition of H. verticillata as much as 85 ± 10 g (P1), 110 ± 10 g (P2) and 135 ± 10 g (P3). The parameters were water quality, survival rate and specific growth rate of catfish. The data were analyzed by regressions analysis, analysis of variance and least significant diference test. The result showed that the addition of H. verticillata could improved water quality. The treatment of addition ofH. verticillata as much as 135 ± 10 g (P3) has highest survival rate 95.49 %, spesific growth rate for length 1.53 %.day-1 and weight 5.25 %.day-1. Keywords: Catfish,  Hydrilla verticillata, Phytoremediation, Water Quality